The contribution of mindfulness in the association between L2 learners’ engagement and burnout - Juan Wu; Qifeng Zhao (Heliyon, 2023)
There has been recently a growing interest in L2 learners' engagement as a central factor in their success. However, not all L2 learners are engaged intellectually, passionately, and behaviorally in L2 learning and this can be due to their experience of burnout in language educational settings. On the other hand, L2 learners frequently encounter heightened degrees of burnout because of emotional and behavioral disengagement. To relieve the relationship between engagement and burnout, the influential technique known as mindfulness, as a coping mechanism for enhancing engagement and reducing burnout among L2 learners, has emerged. Given this conceptual model, the purpose of this paper is to argue the mediator role of mindfulness, in light of self-determination and self-control theory, between L2 students’ engagement and burnout. A few directions for future inquiries are discussed following this review.